Breaking the chains: exploring gender inequality in Türkiye through the eyes of women NGO members - Savas, Gokhan; Çakır, Dilek (Frontiers in Sociology, 2024)
In Türkiye, women’s NGOs have gained significant influence in gender politics, especially since the country’s turn towards neoliberalism. A survey conducted among 735 members of women’s NGOs revealed that, contrary to expectations, many members hold gender inequitable attitudes, highlighting a lack of gender consciousness within these organizations. Key findings indicate that support for gender equality is higher among participants in Ankara than in Istanbul, and that factors such as education, political ideology, and socio-economic status significantly shape these attitudes. The persistence of patriarchal beliefs within these organizations suggests the need for a deeper analysis of the socio-political and structural barriers that hinder gender equality. This study provides critical insights into the intersection of civil society, gender attitudes, and advocacy in Türkiye.